Rancang dan Bangun Aplikasi Pemesanan Sayur dan Buah Berbasis Android: Array - Tanjung, Afrizal (Universitas Harapan Medan, 2021)
Technological development in Indonesia has increased quite rapidly, but many entrepreneurs have not fully utilized technology, including in the sale of vegetables and fruit, so that promotion and market reach is not optimal. The purpose of this study was to build a User Friendly Android-based fruit and vegetable ordering application using the Waterfall method and using the Black Box testing technique so that the application built was easy to use so that it covered a wider market reach. The result of this research is an android-based application in making sales and ordering, making it easier for people to buy and order vegetables and fruit.